Motivasi Belajar Siswa Kelas XI dalam Pembelajaran Beladiri Pencak Silat di SMK Rosma - Kurniawan Kurniawan; Bambang Ismaya; Abdul Salam Hidayat (Peneliti.net, 2022)
This study aims to determine the Learning Motivation of Class XI Students in Learning Pencak Silat at SMK Rosma. This study uses a quantitative approach. If viewed from the type of data presented, the method in this study is a survey research using a questionnaire. The sample used is purposive sampling, totaling 90 students. The results obtained with the category of